2011
DOI: 10.1210/me.2010-0217
|View full text |Cite
|
Sign up to set email alerts
|

Signaling from the Human Melanocortin 1 Receptor to ERK1 and ERK2 Mitogen-Activated Protein Kinases Involves Transactivation of cKIT

Abstract: Melanocortin 1 receptor (MC1R), a Gs protein-coupled receptor expressed in melanocytes, is a major determinant of skin pigmentation, phototype and cancer risk. Upon stimulation by αMSH, MC1R triggers the cAMP and ERK1/ERK2 MAPK pathways. In mouse melanocytes, ERK activation by αMSH binding to Mc1r depends on cAMP, and melanocytes are considered a paradigm for cAMP-dependent ERK activation. However, human MC1R variants associated with red hair, fair skin [red hair color (RHC) phenotype], and increased skin canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
99
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 83 publications
8
99
0
Order By: Relevance
“…Notably, ARRB2 did not impair MC1R functional coupling to the ERK pathway. We have shown that activation of the ERKs by human MC1R relies on the cAMP-independent transactivation of the cKIT receptor tyrosine kinase (Herraiz et al, 2011a). We have also shown that many natural or artificial MC1R mutations decrease MC1R coupling to the cAMP pathway without effects on ERK activation (Herraiz et al, 2012).…”
Section: Competitive Association Of Arrb1 and Arrb2 Isoforms With Mc1rmentioning
confidence: 91%
See 1 more Smart Citation
“…Notably, ARRB2 did not impair MC1R functional coupling to the ERK pathway. We have shown that activation of the ERKs by human MC1R relies on the cAMP-independent transactivation of the cKIT receptor tyrosine kinase (Herraiz et al, 2011a). We have also shown that many natural or artificial MC1R mutations decrease MC1R coupling to the cAMP pathway without effects on ERK activation (Herraiz et al, 2012).…”
Section: Competitive Association Of Arrb1 and Arrb2 Isoforms With Mc1rmentioning
confidence: 91%
“…MC1R is a Gprotein-coupled receptor (GPCR) whose activation triggers the cAMP pathway leading to cAMP-dependent transcriptional activation of microphthalmia transcription factor (Levy et al, 2006). In human melanocytic cells, MC1R also activates the extracellular signal regulated kinases (ERK) 1 and 2 independently of cAMP Herraiz et al, 2011a). Active ERKs phosphorylate Microphthalmia to increase its activity (Hemesath et al, 1998), thereby stimulating transcription of genes encoding for melanogenic proteins.…”
Section: Introductionmentioning
confidence: 99%
“…MITF is the target of MAPK pathway at various levels including its transcription and its protein turnover and function 15,20,21) , which is essential for melanocyte differentiation 25) , and importantly related to malignant progression 31) .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, MC1R is considered as a key factor that plays important roles in the melanocyte transformation process in pathological conditions such as ultraviolet radiation 14) . In melanoma, MC1R is overexpressed on the cell surface of the majority of human melanomas, and correlated with melanoma initiation, progression and metastasis 15) .…”
Section: The Activation Of Mc1r Signaling In Melanocytes Inducesmentioning
confidence: 99%
“…MC3R has been shown to induce inositol phosphate signaling (Konda et al, 1994) and MC5R was reported to activate the Janus kinase/signal transducer and activator of transcription (Jak/STAT) pathway in B cells (Buggy, 1998). Stimulation of all MCRs leads to activation of mitogen-activated protein kinases (MAPK) ERK-1/2 Chai et al, 2007;Herraiz et al, 2011;Patten et al, 2007, Rodrigues et al, 2009Roy et al, 2011). Depending on the cell type this effect may involve phosphoinositol 3 kinase activation (Rodrigues et al, 2009;Vongs et al, 2004).…”
Section: Mcr Signaling Pathwaysmentioning
confidence: 99%